The Strategy Management in (Business) Organization - Nurpida, Lisna (Greenation Research & Yayasan Global Resarch National, 2023)
This paper presents strategic management as an important business managemen, Organizational levels, individuals truly formalize frameworks as a capacity to direct and focus their undertakings. In a business affiliation (a firm), such undertakings will focus in on making an impetus for benefit and coordinating the relationship towards future. The success of organizations is often attributed to effective business strategy. Affiliations really should learn and sort out the conditions as well as the communication for making feasible business procedure. Understanding what method really is and taking on the most effective way to manage cultivate strategy and large around as important as learning about how to make affiliations productive. Business philosophy has seen such endless changes in direction, highlight and approaches.